Computational Intelligence in Data Mining-Volume 1 Proceedings of the International Conference on CIDM, 5-6 December 2015 - Behera, Himansu Sekhar; Mohapatra, Durga Prasad; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book is a collection of high-quality peer-reviewed research papers presented in the Second International Conference on Computational Intelligence in Data Mining (ICCIDM 2015) held at Bhubaneswar, Odisha, India during 5 - 6 December 2015. The two-volume Proceedings address the difficulties and challenges for the seamless integration of two core disciplines of computer science, i.e., computational intelligence and data mining. The book addresses different methods and techniques of integration for enhancing the overall goal of data mining. The book helps to disseminate the knowledge about some innovative, active research directions in the field of data mining, machine and computational intelligence, along with some current issues and applications of related topics.
Chapter 1. A Novel Approach for Biometric Authentication System Using Ear, 2D Face and 3D Face Modalities -- Chapter 2. An Optimal Policy with Quadratic Demand, Time-Varying Quadratic Holding Cost and Partial Backlogging -- Chapter 3. A Novel Approach for Order Reduction of High Order Discrete Time Systems Using Modified Routh Approximation Method via w-Domain -- Chapter 4. Pose Invariant Face Recognition for New Born: Machine Learning Approach -- Chapter 5. Implementation of Data Analytics for MongoDB Using Trigger Utility -- Chapter 6. Heart Disease Prediction Using k-Nearest Neighbour Classifier Based on Handwritten Text -- Chapter 7. Optimizing a Higher Order Neural Network through Teaching Learning Based Optimization Algorithm -- Chapter 8. Deploying a Social Web Graph over a Semantic Web Framework -- Chapter 9. Detecting and Analysing Invariant Groups in Complex Networks -- Chapter 10. Automatic Mucosa Detection inVideo Capsule Endoscopy with Adaptive Thresholding -- Chapter 11. Optimization Approach for Feature Selection and Classification with Support Vector Machine -- Chapter 12. Design and Development of Controller Software for MAS Receiver Using Socket Programming -- Chapter 13. Inference of Replanting in Forest Fire Affected Land Using Data Mining Technique -- Chapter 14. A New Approach on Color Image Encryption Using Arnold 4D Cat Map -- Chapter 15. Neutrosophic Logic Based New Methodology to Handle Indeterminacy Data for Taking Accurate Decision -- Chapter 16. Prognostication of Student's Performance: An Hierarchical Clustering Strategy for Educational Dataset -- Chapter 17. Design and Implementation ACO Based Edge Detection on the Fusion of Hue and PCA -- Chapter 18. Effective Sentimental Analysis & Opinion Mining of Web Reviews Using Rule Based Classifiers -- Chapter 19. Trigonometric Fourier Approximation of the Conjugate Series of a Function of Generalized Lipchitz Class by Product Summability -- Chapter 20. Optimal Energy Efficient Path Selection Using Venus Flytrap Optimization Algorithm in MANET -- Chapter 21. Bi-clustering Using Venus Flytrap Optimization Algorithm -- Chapter 22. Analytical Structure of a Fuzzy Logic Controller for Software Development Effort Estimation -- Chapter 23. Malayalam Spell Checker Using N-Gram Method -- Chapter 24. Sample Classification Based on Gene Subset Selection -- Chapter 25. A Multi Criteria Document Clustering Approach Using Genetic Algorithm -- Chapter 26. Positive and Negative Association Rule Mining Using Correlation Threshold and Dual Confidence Approach -- Chapter 27. Extractive Text Summarization Using Lexical Association and Graph Based Text Analysis -- Chapter 28. Design of Linear Phase FIR Band Stop Filter Using Fusion Based DEPSO Algorithm -- Chapter 29. A Survey on Face Detection and Person Re-identification -- Chapter 30. Machine Translation of Telugu Singular Pronoun Inflections to Sanskrit -- Chapter 31. Tweet Analyzer: Identifying Interesting Tweets Based on the Polarity of Tweets -- Chapter 32. Face-Tracking to Detect Dynamic Target in Wireless Sensor Networks -- Chapter 33. Abnormal Gait Detection Using Lean and Ramp Angle Features -- Chapter 34. Fuzzy Logic and AHP-based Ranking of Cloud Service Providers -- Chapter 35. Classification of Tabla Strokes Using Neural Network -- Chapter 36. Automatic Headline Generation for News Article -- Chapter 37. Identifying Natural Communities in Social Networks Using Modularity Coupled with Self Organizing Maps -- Chapter 38. A Low Complexity FLANN Architecture for Forecasting Stock Time Series Data Training with Meta-Heuristic Firefly Algorithm -- Chapter 39. A Novel Scheduling Algorithm for Cloud Computing Environment -- Chapter 40. PSO Based Tuning of a Integral and Proportional Integral Controller for a Closed Loop Stand-alone Multi Wind Energy System -- Chapter 41. Statistically Validating Intrusion Detection Framework against Selected DoS Attacks in Ad Hoc Networks: An NS-2 Simulation Study -- Chapter 42. Fourier Features for the Recognition of Ancient Kannada Text -- Chapter 43. A Spelling Mistake Correction (SMC) Model for Resolving Real-word Error -- Chapter 44. Differential Evolution Based Tuning of Proportional Integral Controller for Modular Multilevel Converter STATCOM -- Chapter 45. Designing of DPA Resistant Circuit Using Secure Differential Logic Gates -- Chapter 46. Efficient Algorithm for Web Search Query Reformulation Using Genetic Algorithm -- Chapter 47. Throughput of a Network Shared by TCP Reno and TCP Vegas in Static Multi-hop Wireless Network -- Chapter 48. A Pronunciation Rule-based Speech Synthesis Technique for Odia Numerals.
Keywords: Computational intelligence; Data mining; Artificial intelligence; Computational Intelligence; Data Mining and Knowledge Discovery; Artificial Intelligence